The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2217/fca-2020-0225
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics, Virtual Reality and Artificial Intelligence in Heart Failure

Abstract: Aim: Multiomics delivers more biological insight than targeted investigations. We applied multiomics to patients with heart failure (HF) and reduced ejection fraction (HFrEF), with machine learning applied to advanced ECG (AECG) and echocardiography artificial intelligence (Echo AI). Patients & methods: In total, 46 patients with HFrEF and 20 controls underwent metabolomic profiling, including liquid/gas chromatography–mass spectrometry and solid-phase microextraction volatilomics in plasma and urine. HFrE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Similarly, AI-based biomarker discovery using deep phenotyping with multiomics and analysis of digital electrocardiogram and data from wearable devices shows promising results in HF ( 50 ), left ventricular systolic dysfunction ( 51 , 52 ), and arrhythmia ( 53 ). Although reviewing specific applications of AI in cardiovascular contexts exceeds the scope of this review, several interesting review articles address this area ( 54 58 ). Giordano and colleagues discuss the efficacy and application of machine learning and AI in clinical decision making when developing personalized models of patient care ( 59 ).…”
Section: Network Medicine: a Tool For Cardiovascular Disease Researchmentioning
confidence: 99%
“…Similarly, AI-based biomarker discovery using deep phenotyping with multiomics and analysis of digital electrocardiogram and data from wearable devices shows promising results in HF ( 50 ), left ventricular systolic dysfunction ( 51 , 52 ), and arrhythmia ( 53 ). Although reviewing specific applications of AI in cardiovascular contexts exceeds the scope of this review, several interesting review articles address this area ( 54 58 ). Giordano and colleagues discuss the efficacy and application of machine learning and AI in clinical decision making when developing personalized models of patient care ( 59 ).…”
Section: Network Medicine: a Tool For Cardiovascular Disease Researchmentioning
confidence: 99%
“…10 Department of Cardiovascular Medicine, Fukushima Medical University, Fukushima, Japan. 11 Department of Cardiovascular Medicine, Nagoya City University East Medical Center, Nagoya, Japan. 12 Department of Community Medicine for Cardiology, Tokushima University Graduate School of Biomedical Sciences, Tokushima, Japan.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Recently, several researchers reported that advanced imaging can identify subtypes in which treatment was effective [8,9]. An advancing area in this research field is the application of artificial intelligence to carry out detailed phenotyping using multi-omics data, which enables stratification of early-stage diseases and assessment of prognosis [10,11]. Identification of effective subtypes of HF treatment is therefore an essential research topic for optimizing treatment of HF [12].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics refer to global analyses of small molecule metabolites in a biological system ( Nicholson and Lindon, 2008 ). High-throughput metabolomics-based methods have been widely employed for screening novel biomarkers and elucidating the multiple targets and metabolic pathways of heart disease ( Jiang et al, 2020 ; Deidda et al, 2021 ; Gladding et al, 2021 ). Further, metabolic profiling provides integrative information on physiological as well as pathological changes ( Mamas et al, 2011 ; Johnson and Gonzalez, 2012 ).…”
Section: Introductionmentioning
confidence: 99%